Predictors of in-hospital mortality in HIV-infected patients with COVID-19 - Moreno-Torres, Víctor; de Mendoza, Carmen; Martínez-Urbistondo, María; Mills, Patricia; Treviño, Ana; de la Fuente, Sara; Diaz de Santiago, Alberto; Calderon-Parra, Jorge; Pintos, Ilduara; Corpas, Manuel; Soriano, Vicente (QJM: An International Journal of Medicine, 2023)
Background Underlying immunodeficiency is associated with severe COVID-19, but the prognosis of persons with human immunodeficiency virus (HIV) (PWH) with COVID-19 is under debate. Aim: assessment of the mortality rate and major determinants of death in HIV-infected patients hospitalized with COVID-19 in Spain before vaccine availability. Design: Retrospective nationwide public database analysis. Methods Nationwide, retrospective, observational analysis of all hospitalizations with COVID-19 during year 2020 in Spain. Stratification was made according to HIV status. The National Registry of Hospital Discharges was used with the ICD-10 coding list. Results A total of 117 694 adults were hospitalized with COVID-19 during 2020. Only 234 (0.2%) were HIV-positives. More than 95% were on antiretroviral therapy. Compared to HIV-negatives, PWH were younger (mean age 53.2 vs. 66.5 years old; P<0.001) and more frequently male (74.8% vs. 56.6%; P<0.001). Most co-morbidities predisposing to severe COVID-19 (diabetes, hypertension, dementia and cardiovascular disease) were more frequent in HIV-negatives. In contrast, the rate of baseline liver disease was over 6-fold higher in PWH (27.4% vs. 4.4%; P<0.001). In-hospital mortality was lower in PWH (9.4% vs. 16%; P=0.004). In multivariate analysis, older age, dementia and especially advanced liver disease (relative risk (RR): 7.6) were the major determinants of death in PWH hospitalized with COVID-19. Conclusion HIV-infected patients hospitalized in Spain with COVID-19 during 2020 had better survival than HIV-negatives, most likely explained by younger age and lower rate of co-morbidities. However, advanced liver disease was a major predictor of death in PWH hospitalized with COVID-19.
Keywords: Coronavirus Disease 2019; HCV; genotype; JCR; Scopus